Selection of regular direct summands from matrix polynomials - Shavarovskyy, B. Z. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We study the problem of reducibility of matrix polynomials to a quasidiagonal form with regular diagonal blocks by a similarity transformation. The results obtained are applied to solving matrix algebraic equations of Riccati type.